PENGARUH TEKANAN WAKTU, TINDAKAN SUPERVISI, LOCUS OF CONTROL TERHADAP PENGHENTIAN PREMATUR - Aini, Fifi Aprilia Nurul; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out whether there is an influence among time pressure, supervision action, and locus of control to the premature termination on audit procedure. The population is all auditors who work in Public Accountant Office (KAP) in Surabaya. The sample collection technique has been carried out by using purposive sampling. 60 auditors from 7 Public Accountant Offices have been obtained as samples from these criteria. The data analysis techniques are descriptive tests, the data quality test, and the classic assumption tests. The result of this research shows that the time pressure and locus of control variables have positive significant to the premature termination of the audit process. Meanwhile, the supervision action variable has negative influence to the premature termination on audit procedure. Keywords: Time Pressure, Supervision Action, Locus of Control, and The Premature Termination of Audit Procedure.